2005
DOI: 10.1007/s10862-005-3261-3
|View full text |Cite
|
Sign up to set email alerts
|

The Beck Anxiety Inventory in Older Adults With Generalized Anxiety Disorder

Abstract: The authors investigated the psychometric properties of the Beck Anxiety Inventory (BAI) in a sample of 75 older generalized anxiety disorder (GAD) patients and a comparison group of 32 older adults without significant psychopathology. Internal consistency was above .80, and the BAI showed evidence of convergent validity in both groups. Evidence for discriminant validity with respect to measures of depression was weaker. Two items, fearing the worst and nervousness, correctly distinguished 86.5% of patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 27 publications
3
52
0
2
Order By: Relevance
“…Internal consistency is adequate in communitydwelling older adults (Morin et al, 1999;alpha=.89), older psychiatric patients (Kabacoff et al, 1997;alpha=.90), and older medical patients (Steer, Willman, Kay & Beck, 1994;Wetherell & Arean, 1997;alpha=.86 to .92). The BAI demonstrated good convergent validity in older adults with GAD, but, consistent with most measures of anxiety and depression, had poor discriminate validity (Wetherell & Gatz, 2005).…”
Section: Methodsmentioning
confidence: 90%
“…Internal consistency is adequate in communitydwelling older adults (Morin et al, 1999;alpha=.89), older psychiatric patients (Kabacoff et al, 1997;alpha=.90), and older medical patients (Steer, Willman, Kay & Beck, 1994;Wetherell & Arean, 1997;alpha=.86 to .92). The BAI demonstrated good convergent validity in older adults with GAD, but, consistent with most measures of anxiety and depression, had poor discriminate validity (Wetherell & Gatz, 2005).…”
Section: Methodsmentioning
confidence: 90%
“…For example, one comparison of the Beck Anxiety Inventory (BAI; Beck et al, 1988) in older adults with and without GAD found evidence that somatic BAI items frequently reflect medical illness rather than anxiety (Wetherell and Gatz, 2005). Moreover, the BAI, with 21 items, may be too long for use in primary care, especially given the need to assess for other commonly occurring mental health problems such as depression.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that the Persian version of Beck Anxiety Inventory has a good reliability (r=0.72, P<0.001), a very good validity (r=0.83, P<0.001), and an excellent internal consistency (a=0.92). Wetherell and Gatz (2005) explored the psychometric properties of the Beck Anxiety Inventory in a clinical group that included 75 patients with generalized anxiety disorder and a comparison group that included 32 adults without significant psychopathology. They discovered that internal consis-tency was above 0.80 and the Beck Anxiety Inventory showed evidence of convergent validity in both groups.…”
Section: Methodsmentioning
confidence: 99%